Offshoring and labor income risk - Jan Hogrefe; Yao Yao (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper analyzes the impact increased offshoring has on labor income risk. It is therefore distinct from a large number of studies explaining the level effects of globalization on the labor market in that it takes a look at effects on second moments, i.e. the variance of incomes. It provides an assessment that directly connects labor income risk and offshoring trends at the sector level. Importantly, we distinguish between transitory and permanent shocks to individual income. Permanent income risk is defined as variance of shocks to income that do not fade out over time and are assumed to be not self-insurable. It thus has a particular relevance for individual welfare. Our findings suggest that offshoring tends to lower permanent income risk. This effect is particularly strong for offshoring to low-income destinations. Hence, there could be potential welfare gains when domestic firms increasingly offshore production to foreign countries.
urn:nbn:de:bsz:180-madoc-322210
Keywords: F16; F23; E24; 330; trade; offshoring; wages; labor income risk